Shouldering His Guru’s Legacy: Khenpo Tsultrim Lodro’s Discourse in Relation to thos-bsam-sgom after the Death of Khenpo Jigme Phuntsok - Hardie, Catherine (Religions, 2022)
This article contributes to the growing discussion of the ways that Khenpo Jigme Phuntsok’s legacy has been carried forward by his spiritual successors at the Larung Five Sciences Buddhist Academy (or Larung Gar), in contemporary Eastern Tibet, by focusing on the contribution of the Larung vice principal and leading second-generation luminary, Khenpo Tsultrim Lodro (1962-). Drawing on a range of Khenpo Tsultrim Lodro’s spoken teachings and writings over a twenty-year period, this article undertakes a contextualised analysis of how he has shouldered his guru’s legacy in the areas of Tibetan Buddhist monastic education, monastic governance, and monastic-lay relations. It explores how the threefold framework of thos-bsam-sgom (listening, reflecting, meditating), whether in its parts or its entirety, lies at the centre of his reformist discourse in these matters, articulated in relation to a wide range of Buddhist and secular concepts, as well as to concrete institutions and organisational structures. It is argued that, while Khenpo Tsultrim Lodro expounds the entire framework of thos-bsam-sgom throughout the years in question, in ‘the earlier period’ (c.2000-2012), from shortly before his guru’s death until approximately a decade afterwards, he subtly privileges the intellectual attributes associated with thos-bsam, while in ‘the later period’ (c.2013-2021) he reweights his exposition to give a balanced emphasis to the practice of sgom.